Veľká kniha školáčika - Dobšinský, Pavol, 1828-1885; Ďuríčková, Mária, 1919-2004; Feldek, Ľubomír, 1936-; Grimm, Jacob, 1785-1863; Grimm, Wilhelm, 1786-1859; Hevier, Daniel, 1955-; Janovic, Tomáš, 1937-2023; Rázusová-Martáková, Mária, 1905-1964; Podjavorinská, Ľudmila, 1872-1951; Rúfus, Milan, 1928-2009; Seifert, Jaroslav, 1901-1986; Starodubcev, Grigorij, 1982-; et al. (Fifíkova knižnica, 2017)
Krátke básničky, rozprávky po anglicky i po nemecky, jazykolamy, hádanky a pesničky.